Plasma Edge Kinetic-MHD Modeling in Tokamaks Using Kepler Workflow for Code Coupling, Data Management and Visualization (Communications in Computational Physics, 2008)
A new predictive computer simulation tool targeting the development ofthe H-mode pedestal at the plasma edge in tokamaks and the triggering and dynamicsof edge localized modes (ELMs) is presented in this report. This tool brings together, ina coordinated and effective manner, several first-principles physics simulation codes,stability analysis packages, and data processing and visualization tools. A Keplerworkflow is used in order to carry out an edge plasma simulation that loosely couplesthe kinetic code, XGC0, with an ideal MHD linear stability analysis code, ELITE, andan extended MHD initial value code such as M3D or NIMROD. XGC0 includes theneoclassical ion-electron-neutral dynamics needed to simulate pedestal growth nearthe separatrix. The Kepler workflow processes the XGC0 simulation results into simple images that can be selected and displayed via the Dashboard, a monitoring toolimplemented in AJAX allowing the scientist to track computational resources, examine running and archived jobs, and view key physics data, all within a standard Web browser. The XGC0 simulation is monitored for the conditions needed to trigger anELM crash by periodically assessing the edge plasma pressure and current densityprofiles using the ELITE code. If an ELM crash is triggered, the Kepler workflowlaunches the M3D code on a moderate-size Opteron cluster to simulate the nonlinear ELM crash and to compute the relaxation of plasma profiles after the crash. Thisprocess is monitored through periodic outputs of plasma fluid quantities that are automatically visualized with AVS/Express and may be displayed on the Dashboard.Finally, the Kepler workflow archives all data outputs and processed images usingHPSS, as well as provenance information about the software and hardware used tocreate the simulation. The complete process of preparing, executing and monitoringa coupled-code simulation of the edge pressure pedestal buildup and the ELM cycleusing the Kepler scientific workflow system is described in this paper.